2014
DOI: 10.5815/ijigsp.2014.07.01
|View full text |Cite
|
Sign up to set email alerts
|

Applied Computational Engineering in Magnetic Resonance Imaging: A Tumor Case Study

Abstract: This paper solves the biomedical engineering problem of the extraction of complementary and/or additional information related to the depths of the anatomical structures of the human brain tumor imaged with Magnetic Resonance Imaging (MRI). The combined calculation of the signal resilient to interpolation and the Intensity-Curvature Functional provides with the complementary and/or additional information. The steps to undertake for the calculation of the signal resilient to interpolation are: (i) fitting a poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Indeed, filtering is here performed through the CC and the ICF images which are treated as filter masks. The CC and the ICF images can build the visually perceptible third dimension which can highlight the tumor structures and anatomy of the human brain (see also Figures 5e and 5f in previous work [21] as far as regards the ICF). The meaning and the nature of the visually perceptible third dimension in the CC and the ICF images is the capability to filter the MRI.…”
Section: The Literature In Reference To the Research Effortmentioning
confidence: 94%
See 1 more Smart Citation
“…Indeed, filtering is here performed through the CC and the ICF images which are treated as filter masks. The CC and the ICF images can build the visually perceptible third dimension which can highlight the tumor structures and anatomy of the human brain (see also Figures 5e and 5f in previous work [21] as far as regards the ICF). The meaning and the nature of the visually perceptible third dimension in the CC and the ICF images is the capability to filter the MRI.…”
Section: The Literature In Reference To the Research Effortmentioning
confidence: 94%
“…As already seen in Figures 1, 2 and 3, the analogy between the images shown in Figure 6 Figure 6, likewise shown already in Figures 3 and 4, the filtered images in (e), (f) and (g) appear illuminated in a similar fashion seen already in previous research through the signal resilient to interpolation. [21] This aspect will become more apparent in (1) a contrast-brightness effect which makes it possible to highlight the features of the intra-ventricular tumor; and (2) the imaging of the sulci and gyri, which makes it possible to observe the anatomy the details of the brain cortex.…”
Section: The Main Evidencementioning
confidence: 99%
“…In order to frame into the literature the works of this research, which recalls works reported earlier [7,[12][13][14][15][16][17], it is necessary to consider the rationale of the study presented in this paper. So far, no studies have been reported attempting to achieve the characterization of the intensity-curvature term before interpolation.…”
Section: The Scope Of the Researchmentioning
confidence: 99%
“…This paper is concerned with the calculation of the classic-curvature image [12] and the calculation of the intensity-curvature functional term before interpolation image [13][14][15][16][17] using MRI data consisting of a twodimensional image of a human brain affected by a tumor.…”
Section: A the Literaturementioning
confidence: 99%
See 1 more Smart Citation